Glycaemic Control and Long-Term Outcomes following Transition from Modified Intensive Insulin Therapy to Conventional Glycaemic Control. Issue 2 (March 2014) - Orford, N. R.; Bailey, M.; Kaukonen, K.; Elderkin, T.; Stow, P. J.; Cattigan, C.; Kotowicz, M.; Bellomo, R.
This retrospective observational cohort study compared glycaemic control and long-term outcomes following transition from a modified intensive insulin therapy (mIIT) regimen to conventional glycaemic control (CGC) in adult patients admitted to a tertiary adult general intensive care unit, during two 24-month periods, before and after the publication of the Normoglycemia in Intensive Care Evaluation and Surviving Using Glucose Algorithm Regulation (NICE-SUGAR) trial. The before NICE-SUGAR cohort received mIIT (target glycaemic ranges 4.4 to 7.0 mmol/1), while the after NICE-SUGAR cohort received CGC (target glycaemic range 7.1 to 9.0 mmol/1). A total of 5202 patients were included in the study. With transition from mIIT to CGC, the mean time-weighted glucose increased from 6.94 mmol/1 to 8.2 mmol/1 ( P <0.0001). A similar increase was observed in other glycaemic indices (mean, highest and lowest glucose values, P <0.0001 for all). The adjusted 90-day odds ratio for mortality decreased by 47% with transition from mIIT to CGC (odds ratio 1.47 (95% confidence interval, 1.22 to 1.78) (P <0.0001). The rate of severe and moderate hypoglycaemia also decreased from 1.2 to 0.4% ( P =0.004) and from 23.3 to 5.9% (P <0.0001), respectively. mIIT was associated with an increased risk of moderate and severe hypoglycaemia compared to CGC (odds ratio 3.1 (1.51 to 6.39) ( P =0.002), 6.29 (5.1 to 7.75) (P <0.0001)). Changes in recommended glycaemic control were translated into practice, with increased glycaemic indices and decreased rates of severe and moderate hypoglycaemia after the introduction of CGC. The associated decrease in 90-day mortality suggests mIIT was not superior to CGC, despite a lower hypoglycaemia rate than in previous IIT trials. Our findings support the continued use of CGC.